The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1155/2016/8583963
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Functions and Functional Performance among Older Persons with and without Low Back Pain

Abstract: This study aims to compare muscle functions and functional performances between older persons with and without low back pain (LBP) and to determine the association between muscle functions and functional performances. This is a cross-sectional study, involving 95 older persons (age = 70.27 ± 7.26 years). Anthropometric characteristics, muscle functions, and functional performances were measured. Data were analyzed using ANOVA, Pearson's correlation, and multiple linear regression. The functional performances s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Considering the lower limit of the 95% CI for safety purposes (48.2 Nm), proper loading of the LuTxRs' back muscles with 40% of the maximum at the beginning of a training intervention would correlate with 19 Nm on a David back extension device. These data may be consistent with those from healthy women and older female patients with low back pain 16 , 17 but the onset and slope of the regression that served as the basis of the strength translation may change with the patients' individual training state and type of physical activity. Thus, it is important to note that our findings apply exclusively to LuTxR in the subacute phase of rehabilitation.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Considering the lower limit of the 95% CI for safety purposes (48.2 Nm), proper loading of the LuTxRs' back muscles with 40% of the maximum at the beginning of a training intervention would correlate with 19 Nm on a David back extension device. These data may be consistent with those from healthy women and older female patients with low back pain 16 , 17 but the onset and slope of the regression that served as the basis of the strength translation may change with the patients' individual training state and type of physical activity. Thus, it is important to note that our findings apply exclusively to LuTxR in the subacute phase of rehabilitation.…”
Section: Discussionsupporting
confidence: 75%
“…Previous authors found that handgrip strength is a reliable tool, and it provides an estimate of back extension strength in healthy women and in older female patients with low back pain. 16 , 17 In addition, it has been recommended to diagnose sarcopenia 18 and to classify quality of life in postmenopausal osteoporosis as well as the risk of functional deficits in various medical conditions. 19 Dynamometry is easily available, quickly done, and almost free from risk of adverse events.…”
mentioning
confidence: 99%
“…Hershkovitz et al [21], in their research, indicated that higher HGS was associated with better rehabilitation in patients with hip fracture. Ishak et al observed that women with low back pain had poorer HGS compared to those of healthy (P= 0.04), while they did not nd any association between HGS and low back pain in men (P= 0.834) [26]. Findings of another cross-sectional study showed a relationship between muscle strength and low back pain in female health care staff, although this pain did not limit their work activity [27].…”
Section: Discussionmentioning
confidence: 94%
“…Hershkovitz et al [22], in their research, indicated that higher HGS was associated with better rehabilitation in patients with hip fracture. Ishak et al observed that women with low back pain had poorer HGS compared to those of healthy (P= 0.04), while they did not nd any association between HGS and low back pain in men (P= 0.834) [26]. Findings of another cross-sectional study showed a relationship between muscle strength and low back pain in female health care staff, although this pain did not limit their work activity [27].…”
Section: Discussionmentioning
confidence: 94%